The Impact of Advertising on the Consumer Behavior of Diyala University Professors (Survey Study) (Eurasian Journal of Media and Communications, 2026)
The study aimed to identify the impact of commercial advertisements on the consumer behavior of the University of Diyala professors by analyzing the nature of the relationship between exposure to commercial advertisements (digital and traditional) and the consumer behavior of university professors, by identifying the advertising factors that most affect the purchasing decisions of the University of Diyala professors